Multicultural Education in Multicultural Community: A Case Study at Palm Kids Elementary School - Akhmad Saefudin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Character education plays a crucial role in fostering tolerance and harmony in multicultural environments. This study explores the implementation of character building at Palm Kids Elementary School, Purwokerto, Central Java, a school with students from diverse religious backgrounds. This qualitative research employs a case study approach. Data was collected through interviews, observations, and documentation. Analysis was conducted using the Interactive Model of Miles and Huberman. Findings indicate that Palm Kids Elementary School successfully maintains harmony despite religious diversity (Islam, Confucianism, Christianity, Catholicism, Hinduism, Buddhism). A key factor in sustaining this harmony is the comprehensive character education program, which is systematically integrated into daily activities. Additionally, the school organizes inclusive events, such as interfaith holiday celebrations, that encourage participation and understanding among students. Tolerance and mutual respect are instilled from an early age through daily habituation, preventing conflicts related to ethnicity, religion, race, or inter-group differences. The school’s approach aligns with global efforts to promote peace and unity in educational settings. The character-building model at Palm Kids Elementary School serves as a practical framework for fostering tolerance in multicultural school environments. Its implementation could be beneficial for schools worldwide seeking to enhance social harmony among diverse student populations.